Effect of sintering profiles on the properties and ageing resistance of Y-TZP ceramic - Sivakumar, S.; Ramesh, Singh; Chin, K.L.; Tan, C.Y.; Teng, W.D. (Universiti Malaysia Pahang, 2011)
A commercially available Y-TZP ceramic powder was fabricated under four different sintering profiles in order to investigate the effects of conventional single-stage sintering (SSS) with dwell times of 1 min and 2 h, respectively, compared with two-stage sintering (TSS), on the physical and mechanical properties of Y-TZP. Sintering was performed up to 1400oC at a ramp rate of 10oC/min. It was revealed that samples sintered via TSS yielded better properties than the SSS samples sintered at 1400oC using a dwell time of 2 h. In the hydrothermal ageing test, TSS samples did not undergo low-temperature degradation via the tetragonal to monoclinic phase transformation. Nevertheless, it was found by XRD analysis that Y-TZP ceramics sintered by the SSS method using a short dwell time of 1 min were effective in maintaining tetragonal phase stability after 50 h of exposure to superheated steam conditions.